PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG DAN PERTUMBUHAN PENJUALAN TERHADAP LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - SUTARDI SUTARDI; NUR KHASANAH (Universitas Pamulang, 2018)
This research aims to know the influence of rotation of the inventory, accounts receivable turnover and profit on sales growth against pharmaceutical companies. This testing is carried out using Eviews application Version 8.1. Analysis of the multiple linear regression was used. The results showed that the partial inventory turnover have a significant effect on earnings, receivables turnover no significant effect on earnings and sales growth has no significant effect on earnings.Simultaneously the results showed that the rotation of the inventory, accounts receivable turnover and sales growth effect significantly to profits. The magnitude of the coefficient of determination (adj. R2) is 0.850105. This means that a bound variable i.e. 85.01% profit can be explained by three free variables i.e. accounts receivable turnover, inventory turnover and sales growth. While the rest of 14.99% explained by other variables which are not entered into the model.